SEPAKBOLA SEBAGAI BENTUK BARU KOMUNIKASI POLITIK INDONESIA - Kiki Esa Perdana (Jurnal Riset Komunikasi, 2021)
Football is a very popular sport in Indonesia, many people are interested in knowing more about their favorite team in various aspects. This phenomenon is seen as attractive by political elites as an opportunity that makes them profitable, football can be used as a useful political communication medium, especially during electoral politics. This research uses descriptive qualitative research methods, which can be described as a series of research activities that aim to obtain data results that are pure without being in certain conditions, which results emphasize a meaning, not a number. using observation data collection techniques, interviews, documents, and studies literature. The results of this study indicate that political communication over time has shown many changes, especially in the media used, starting from the beginning which was limited to conventional media until now to football.